MODERN ARCHITECTURE APPLICATION ON WEDDING CENTRE DESIGN IN SURAKARTA - Ivana Thalia; Made Suastika; Leny Pramesti (ARSITEKTURA, 2018)
Modern architecture is an approach in the field of architectural engineering that is used as a design approach. The research is done to discuss the field of architectural engineering, especially in planning and design. The purpose of this research is to reveal the concept of planning and design on the application of modern architecture as a design method in Wedding Center building in Surakarta. The method used is a descriptive explorative method on the preparation of planning and modern architecture design methods on the building design. Modern architectural design method is used as a method of design approach on building Wedding Center in Surakarta in order to be able to provide a building image in accordance with the concept of Wedding Center building as a one-stop wedding service in Surakarta. The results and discussion of analysis in this research are qualitative analysis. The final concept formed from this research is a conceptual model and the physical design model of Wedding Center with Modern Architecture Approaches in Surakarta.